Effect of Climate Variability on Chili Pepper (Capsicum frutescens L.) Cultivation in Indonesia: 10.32526/ennrj/23/20250097 - Nugroho, Bayu Dwi Apri; Ardhitama, Aristya; Sartohadi, Junun; Qadafi, Muamar; Siswoko, Bowo Dwi; Adilah, Afifatul Husna Al (Environment and Natural Resources Journal, 2025)
Significant shifts in climate patterns, particularly in rainfall and frequency of rainy days, are factors contributing to high variability in cultivation of agricultural products such as chili peppers. Therefore, this study investigated the impact of seasonal climate variability on chili pepper (Capsicum frutescens L.) production in Sleman Regency, of Central Java, Indonesia. Statistical methods including analysis of variance (ANOVA), principal component analysis (PCA), and Pearson correlation were used to examine the influence of various climate and seasonal factors such as rainfall, air temperature, humidity, rainy days, dry season onset, and duration on chili productivity. The results showed that total rainfall and frequency of rainy days significantly affected chili productivity, with correlation coefficients of +0.579 and +0.492 (p<0.05), and ANOVA confirming a strong relationship (F=260.75, p<0.001). This showed that rainfall distribution and frequency were critical factors influencing yield variability. Statistical analyses correlated with climate variability index calculations further confirmed significant climate changes in the region. Based on the results, both total rainfall and seasonal distribution were critical factors influencing chili pod productivity, emphasizing the importance of agricultural planning and adaptation strategies under changing climate conditions. The novelty of this study was in local-scale seasonal analysis, which used a climate variability index to detect extreme variability. When combined with multivariate statistical triangulation (correlation, PCA, and ANOVA), it offered robust evidence for region-specific adaptation strategies for chili farmers. The results showed the importance of including climate indicators in agricultural policy planning. Moreover, further studies were recommended to explore spatial climate trends across broader regions.